Novel Co3O4 Nanoparticles/Nitrogen-Doped Carbon Composites with Extraordinary Catalytic Activity for Oxygen Evolution Reaction (OER) - Yang, Xiaobing; Chen, Juan; Chen, Yuqing; Feng, Pingjing; Lai, Huixian; Li, Jintang; Luo, Xuetao (Nano-Micro Letters, 2017)
Herein, Co3O4 nanoparticles/nitrogen-doped carbon (Co3O4/NPC) composites with different structures were prepared via a facile method. Structure control was achieved by the rational morphology design of ZIF-67 precursors, which were then pyrolyzed in air to obtain Co3O4/NPC composites. When applied as catalysts for the oxygen evolution reaction (OER), the M-Co3O4/NPC composites derived from the flower-like ZIF-67 showed superior catalytic activities than those derived from the rhombic dodecahedron and hollow spherical ZIF-67. The former M-Co3O4/NPC composite displayed a small over-potential of 0.3 V, low onset potential of 1.41 V, small Tafel slope of 83 mV dec−1, and a desirable stability. (94.7% OER activity was retained after 10 h.) The excellent performance of the flower-like M-Co3O4/NPC composite in the OER was attributed to its favorable structure. Highlights: 1 Co3O4 nanoparticles/nitrogen-doped carbon (Co3O4/NPC) composites were successfully fabricated from zeolitic imidazolate framework 67 (ZIF-67), and the composite structure could be well controlled by adjusting the structure of ZIF-67. 2 M-Co3O4/NPC composites derived from flower-like ZIF-67 showed the highest activities for the oxygen evolution reaction (OER).